The Effect of Transformational Leadership Style on Job Satisfaction with Trust-In-Leader as Intervening Variable - Muslichah Muslichah; Sobikhul Asrori (Journal of Innovation in Business and Economics, 2018)
This research was aimed to analyze direct and indirect effects of transformational leadership style on job satisfaction. The population of research included all employees at the Local Secretariat Office of Pasuruan Indonesia, which was counted for 170 persons. A questionnaire was distributed to this population, and 151 questionnaires were returned, which thus resulting in a response rate of 88.82%. Data analysis procedure is path analysis facilitated by a PLS computer software. Results indicated that: 1) There is a direct, positive and significant effect of transformational leadership style on job satisfaction; 2) There is a direct, positive, and significant effect of transformational leadership style on trust-in-leader; 3) There is a direct, positive, and significant effect of trust-in-leader on job satisfaction; 4) Trust-in-leader mediates the effect of transformational leadership style on job satisfaction. Given all these findings, this research not only has a good implication on practice but also to the  literature concerning the effect of both transformational leadership style and trust-in-leader on job satisfaction. It is also expected that this research provides information that can be used as guidance by the Local Secretariat Office in Pasuruan City Indonesia when it decides to improve employee’s job satisfaction.